APLIKASI DOE UNTUK MENENTUKAN SETTING PARAMETER OPTIMUM PADA PROSES PEMBUATAN PRODUK ROLL - Anggoro, Paulus Wisnu (MEDIA STATISTIKA, 2012)
Problem faced by Atmaja Jaya Industry, Klaten is how to produce high quality products with Â Â Â Â Â Â Â Â Â a minimal amount of defective products. Therefore, this study will look at factor that affect the quality of roll 6â€ TL in order to obtain the best level setting in the production process. This study uses experimental design with the Taguchi method. Factors to be tested in this study is long making liquid metal (factor A), the old foundry (factor B), and total time of casting (factor C). Each factor has three levels so that the use of orthogonal array L934. From the result of pooling up mean, the best level combination of factors that affect the quality of roll 6â€TL is the length of manufacture of liquid metal which set at 100 minutes, the old foundry is set at 5 seconds and the total time of casting that set in 14 minutes. While the result of pooling up SN ratio for the best level combination of factors that affect the quality of production process variants roll 6â€TL which the length of the manufacture of liquid is set at 100 minutes and total time of casting that are set in 14 minutes. Keywords: Taguchi Method, Orthogonal Array, Roll 6â€ TL, Product defect